Effect of resistivity on the pedestal MHD stability in JET. (1st December 2022) - Nyström, H.; Frassinetti, L.; Saarelma, S.; Huijsmans, G.T.A.; Perez von Thun, C.; Maggi, C.F.; Hillesheim, J.C.; contributors, JET
Abstract: The ELM triggering mechanism in tokamaks is not yet fully understood. For example, in the JET tokamak with ITER-like wall (commonly called JET-ILW), the ELMs are sometimes triggered before the ideal peeling-ballooning (PB) boundary is reached. This typically occurs for shots with high input power and high gas rate. The discrepancy between model and experiment has in previous works been clearly correlated with the relative shift between the electron temperature and density pedestals. The discrepancy has also been correlated with the resistivity in the middle-bottom of the pedestal. The present work shows that resistive MHD can have a significant impact on the PB stability of JET pedestals. The inclusion of resistivity removes the correlation between the discrepancy from the PB stability and the relative shift (the difference between the position of the electron temperature and density pedestals) and significantly improves the agreement between PB model and experimental results. The work also shows that the key parameter is the resistivity at the pedestal bottom, near the separatrix, while the resistivity near the middle/top of the pedestal has a negligible effect on the PB stability of JET plasmas.